Application of HPLC‐LTQ Orbitrap MS for metabolic profiles of Polygonum multiflora extract in rats. (14th September 2017) - Zhang, Jing; Wang, Tenghua; Ren, Zhiyao; Gong, Lu; Huang, Juan; Bai, Junqi; Qiu, Xiaohui; Xu, Wen
Abstract: The root of Polygonum multiflorum (PM) is an important Chinese herbal medicine for treatment of various diseases. Extensive pharmacological studies have been conducted and demonstrated that it shows a wide range of bioactivities. Meanwhile, a considerable number of hepatotoxicity cases owing to oral administration of PM have been reported and have attracted great attention. However, the limited knowledge regarding the metabolism of PM restricts the deeper studies on its pharmacological/toxicological mechanism and therapeutic material basis. The present study aimed to develop a high‐performance liquid chromatography coupled with a linear ion trap–Orbitrap hybrid mass spectrometry method for separation and identification of metabolites in rat urine and plasma after oral administration of PM . Based on the proposed strategy, metabolism profiles of PM in rats were proposed for the first time and 43 metabolites were characterized or tentatively identified. Phase II metabolism, such as glucuronidation and sulfation, are the principal pathways of the main components. These findings will be beneficial to further understanding of the pharmacological mechanism and pharmacodynamic material basis of PM.